Factors Influencing Consumers’ Intention To Adopt Hybrid Electric Vehicles (HEV) In Malaysia - Oo, Yew Che Yin @ Kathy (2022)
The main purpose of this study is to investigate the factors that influence the adoption of hybrid vehicle . A total of s in Malaysia . This study also aims to contribute to a better understanding of the consumers behaviour that leads to the adoption of hybrid vehicles 211 usable questionnaires were coded and techniques such as descriptive analysis, indepe analysed ndent samples t. Statistical test, oneway ANOVA, factor analysis, and regression analysis were used in this study. The regression analysis results showed that relative advantage, compatibility, pro environmental, and subjective norms were positively related to the adoption of hybrid cars in Malaysia. However, have a perceived behavioural control relationship with the adoption of hybrid vehicles. was found not to Attitudinal factors and perceived behavioural control are important determinants for the adoption of hybrid vehicles. Marketers can use these results to segment their market. Future study should look into the factors influencing the adoption of hybrid vehicles by users rather than potential users.